Análisis del clima organizacional y creación del departamento de talento humano en la Empresa Dibraxi S.A. año 2015 - Gamarra Avilés, Jessica Leonor (2015)
The company Dibraxi S.A., is located in the city of Quevedo, Los Rios Province in the Citadel San Jose, Av. Jaime Roldós Aguilera Aprocico building being General Manager Mr. Homero Gamarra Avilés. At present the company present problems indoles and administrative directly related to the human talent due to lack of strategic direction by the owners who are responsible for decision making in the company, thus affecting the performance of its employees at the same time generates a low commitment from them to not feel part of it. One of the main reasons is that the company does not have an area where human talent to correctly manage this problem directly affects decision-making and that human resources feel dissatisfied by the provisions that are taken by of managers, causing discomfort and affecting the performance of its employees. The aims and purposes of an adequate organizational climate will lead to maintaining a high level of responsibility to direct skills between management and employees, will also create opportunities for promotion which will lead to a proposal is designed to implement a department of human talent to manage responsibly the company workers Dibraxi S.A. with confidence and addressing for the proper performance of their duties. This is expected to contribute significantly to research the company Dibraxi S.A. way, and that will have a strategic tool provided from an area that is responsible for properly managing human talent, research was developed through the design goals that marked the route to continue to draw conclusions and recommendations, for this was necessary to have a methodological framework with the implementation of materials, techniques, sources and methods of investigation to the presentation of results through data provided by the employees and executives of the company this allowed the direct analysis of the organizational climate and the design of a proposal to create the department of human talent, which justifies the development of this research. KEY WORDS: Organizational climate - human talent - development model of organizational climate - creation of the department of human resources.